Julián Ríos’ "Larva. Babel de una noche de San Juan", or Don Juan Tenorio’s vertigo of identities - Faiano, Alessia (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The aim of this article is to relate the myth of Don Juan Tenorio with Julián Rios’s novel Larva. Babel de una noche de San Juan. Starting from the analysis of the essential functions that constitute this literary myth, these pages will examine how our author appropriates them to build a very personal and complex book, that breaks with the patterns of the traditional novel.